The Effect of Teacher Engagement on Student Boredom in Elementary School: Implications for School Counseling Practices - Tul'adawiyah, Ropiah; Nurihsan, Juntika; Budiman, Nandang (KONSELOR, 2024)
This study aims to determine the effect of teacher involvement on elementary school students' boredom and its implications for guidance and counseling practices in schools. Using a quantitative approach with a correlational design, data were collected from 454 elementary school students in Bandung City who completed questionnaires on teacher engagement and boredom levels. The results of the analysis showed that teacher engagement, especially on the emotional aspect, has a negative influence on student boredom, i.e. the higher the teacher engagement, the lower the student boredom. This finding highlights the importance of the teacher's role in creating an active and interactive learning atmosphere to reduce student boredom. The practical implication is that school counselors can support teachers by providing training to strengthen emotional and cognitive engagement and encourage the development of students' social skills to create a conducive and enjoyable learning environment. This study recommends further research to explore other factors that influence student boredom and to examine the influence of teacher engagement in different educational contexts.